Size exclusion chromatography for the characterization and quality control of biologics. Issue 5 (3rd April 2021) - Singh, Surinder M.; Furman, Ran; Singh, Rajesh K.; Balakrishnan, Gurusamy; Chennamsetty, Naresh; Tao, Li; Li, Zhengjian
Abstract: Size exclusion chromatography (SEC) is a powerful tool for analyzing size variants of proteins in academic and biopharmaceutical laboratories. Recent advancements in SEC methodology have improved size separation range, resolution, and sensitivity for analytes of interest. SEC analysis augmented with various detectors including light scattering, fluorescence, refractive index (RI), viscometer, and mass spectrometry, in-line with the classical UV-Vis detector has dramatically expanded its capabilities for characterizing primary and higher order structures, post translational modifications (PTMs), and other physicochemical attributes of biologics in a single analytical method. This review provides a brief account of recent advancements in the stationary and mobile phases, detectors, and applications in biopharma industry. Finally, a brief discussion on the applications of SEC in process development and quality control of protein therapeutic products, along with the challenges and corresponding mitigation strategies is provided. Graphical Abstract: UF0001